Oceanographic Data of the 37th Japanese Antarctic Research Expedition from November 1995 to March 1996 - オイカワ, コウシロウ; ミウラ, ユキヒロ; OIKAWA, Koushiro; MIURA, Yukihiro (National Institute of Polar Research, 1999)
P(論文) The results of oceanographic observations on board the icebreaker "Shirase" and tidal observations at Syowa Station, Antarctica, are presented in this report. The oceanographic observations were carried out by the summer party of the 37th Japanese Antarctic Research Expedition (JARE-37) during the austral summer of 1995/1996. The tidal observations were carried out by the winter party of JARE-36 from February 1995 to January 1996. departmental bulletin paper